Μηχανική συμπεριφορά σύνθετων υλικών με ίνες άνθρακα υποστατικά και επαναλαμβανόμενα φορτία - Δεληγιαννίδου, Μαρία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2017)
The main scope of the present thesis is the experimental evaluation of the mechanical properties of two new composite materials that are about to be used in the structure of a regional aircraft. Manufacturing of the composites has been performed in the Advanced Composites Laboratory of Hellenic Aerospace Industry in pre-defined dimensions according to the respective International specifications. The experimental tests were performed in the same Laboratory as well as in Laboratory of Strength and Materials of School of Applied Physical Sciences and mathematics, National Technical University of Athens.